Polypyrrole-modified mushroom residue activated carbon for sulfate and nitrate removal from water: Adsorption performance and mechanism. (October 2022) - Li, Hongyan; Chai, Lina; Cui, Jianguo; Zhang, Feng; Wang, Fang; Li, Shangming
Abstract: A new type of adsorption material, polypyrrole-modified mushroom residue activated carbon (Ppy-MRAC), was prepared by compounding MR in agricultural waste and Ppy using a dipping method. A characterization analysis indicated that Ppy-MRAC is a mesoporous material, containing functional groups such as hydroxyl (OH − ) and coordinated chloride (Cl − ) ions. The efficacy of Ppy-MRAC for removing sulfate (SO4 2− ) and nitrate (NO3 − ) from water was studied. The experimental results showed that the adsorption of SO4 2− and NO3 − by Ppy-MRAC followed the Langmuir and pseudo-second-order kinetic models, with maximum adsorption capacities of 40.00 and 51.55 mg/g, respectively. The removal rates of 500 mg/L SO4 2− at 35 °C and 50 mg/L NO3 − at 15 °C were 31.53% and 82.65%, respectively. A thermodynamic analysis revealed adsorption of SO4 2− and NO3 − via spontaneous endothermic and exothermic reactions, respectively. The adsorption mechanisms were mainly electrostatic attraction, ion exchange, and hydrogen bond. The Ppy-MRAC could be regenerated six times after being eluted by NaOH. Low-cost Ppy-MRAC had a high removal rate for inorganic salts in simulated wastewater, and strong environmental and economic benefits. Graphical abstract: Unlabelled Image Highlights: Ppy-MRAC composite material was prepared by Polypyrrole-modified mushroom residue activated carbon. SO4 2− and NO3 − adsorption on Ppy-MRAC fitted the Langmuir and pseudo-second-order models. Electrostatic attraction, ion exchange, and hydrogen bond were the key adsorption mechanism. Ppy-MRAC is a low-cost and environmentally sustainable adsorbent for SO4 2− and NO3 − removal. Efficient utilization of agricultural waste mushroom residue